Biomass Production of High Density Leucaena leucocephala Plantation under different levels of nutrients - Singh, Baljit; Dhillon, G.P.S.; Gill, R.I.S.; Kaur, Janpriya (Indian Forester, 2019)
High density subabul (Leucaena leucocephala) plantations are being raised in Punjab for biomass based electricity generation. An experiment was conducted at PAU Ludhiana to standardize the nutrient requirement of high density (1 x 1 m) plantation of subabul for its high biomass production. Six combinations of nitrogen, phosphorus and potassium viz. 0:0:0 (control), 20:20:10, 40:40:20, 60:60:30, 80:80:40 and 100:100:50 kg/ha N:P2 O2 :K2 O were tested. The data on growth parameters (collar diameter, height and branch numbers), fresh and dry biomass of stems, branches, leaves and total biomass were recorded one year after planting and subsequently that of six month old coppice shoots. Collar diameter and plant height after one year growth were minimum (1.92 cm and 2.51 m, respectively) without application of nutrients while maximum (2.63 cm and 3.68 m, respectively) with the application of N:P2 O2 :K2 O 40:40:20 kg/ha. The total fresh biomass after one year growth and six month old coppice shoots was significantly higher by applying N:P2 O2 :K2 O 40:40:20 kg/ha (14.98 and 22.36 t/ha, respectively) than other nutrient levels. The stems, branches, leaves and total dry biomass after one year growth was the lowest (2.92, 0.86, 1.36 and 5.15 t/ha, respectively) without nutrient application and significantly highest with the application of N:P2 O2 :K2 O 40:40:20 kg/ha (3.75, 0.95, 1.79 and 6.49 t/ha, respectively). Fresh and dry biomass of six month old coppice shoots was higher than the biomass of previous one year. Thus, it is advisable to apply nutrients 40:40:20 kg/ha N:P2 O2 :K2 O every year to obtain maximum production of high density subabul plantation.